Active vaccination attenuates the psychostimulant effects of α-PVP and MDPV in rats. (April 2017) - Nguyen, Jacques D.; Bremer, Paul T.; Ducime, Alex; Creehan, Kevin M.; Kisby, Brent R.; Taffe, Michael A.; Janda, Kim D.
Abstract: Recreational use of substituted cathinones continues to be an emerging public health problem in the United States; cathinone derivatives α-pyrrolidinopentiophenone (α-PVP) and 3, 4-methylenedioxypyrovalerone (MDPV), which have been linked to human fatalities and show high potential for abuse liability in animal models, are of particular concern. The objective of this study was to develop an immunotherapeutic strategy for attenuating the effects of α-PVP and MDPV in rats, using drug-conjugate vaccines created to generate antibodies with neutralizing capacity. Immunoconjugates (α-PVP-KLH and MDPV-KLH) or the control carrier protein, keyhole limpet hemocyanin (KLH), were administered to groups (N = 12) of male Sprague-Dawley rats on Weeks 0, 2 and 4. Groups were administered α-PVP or MDPV (0.0, 0.25, 0.5, 1.0, 5.0 mg/kg, i.p.) in acute drug challenges and tested for changes in wheel activity. Increased wheel activity produced by α-PVP or MDPV in the controls was attenuated in the α-PVP-KLH and MDPV-KLH vaccinated groups, respectively. Rectal temperature decreases produced by MDPV in the controls were reduced in duration in the MDPV-KLH vaccine group. A separate group (N = 19) was trained to intravenously self-administer α-PVP (0.05, 0.1 mg/kg/inf) and vaccinated with KLH or α-PVP-KLH, post-acquisition. Self-administration in α-PVP-KLH rats was initially higher than in the KLH rats but then significantly decreased following a final vaccine booster, unlike the stable intake of KLH rats. The data demonstrate that active vaccination provides functional protection against the effects of α-PVP and MDPV, in vivo, and recommend additional development of vaccines as potential therapeutics for mitigating the effects of designer cathinone derivatives. Highlights: The novel drugs alpha-pyrrolidinopentiophenone (α-PVP) and 3, 4-methylenedioxypyrovalerone (MDPV) have high abuse potential. There are no currently available therapies to treat stimulant abuse, including MDPV and α-PVP. Drug-conjugate vaccines were created to generate antibodies to neutralize MDPV and α-PVP. Increased wheel activity was produced by α-PVP or MDPV in the controls but not the vaccinated groups. Self-administration of α-PVP was disrupted in the vaccinated group.